Widespread Cutaneous Indeterminate Dendritic Cell Tumor (IDCT) With ETV3::NOAC2 Rearrangement Successfully Treated With PUVA Therapy: A Case Report - Akshay Deshpande; Zbigniew Rudzki; Jaideep Bhat; Matthew Pugh; Susan Rose; Shankara Paneesha (Case Reports in Hematology)
The unique histiocytic entity of indeterminate dendritic cell tumor (IDCT) is known to cause diagnostic conundrum and treatment dilemmas with no published consensus on either. We report a rare case of cutaneous IDCT with ETV3::NOAC2 rearrangement providing further evidence to its association with this condition. With its ease of administration and minimal side effects, PUVA therapy can be successfully used to treat cutaneous forms of IDCT.